2020
DOI: 10.1111/joca.12330
|View full text |Cite
|
Sign up to set email alerts
|

Who has a cushion? The interactive effect of social exclusion and gender on fixed savings

Abstract: Saving behavior affects both personal welfare and national economies. This study examined the effect of social exclusion, a breakdown of social relationship, on fixed savings, which is especially pertinent to Asians. By considering the cushion hypothesis theory and the gender disparity in social connectedness, this study proposes that men and women display different fixed savings behavior in response to social exclusion. In particular, social exclusion (vs. acceptance) decreases men's fixed savings intention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…In both experiments, social exclusion was manipulated through a Cyberball game (Williams & Jarvis, 2006). Many previous studies 1 (Fan & Jiang, 2018;Mathes & Schmidt, 2020;Yang et al, 2020) have used this tool and demonstrated its reliability. Furthermore, because we conducted online experiments, using Cyberball made it convenient for researchers and participants to complete the experimental process.…”
Section: Manipulation Technique (Cyberball)mentioning
confidence: 99%
“…In both experiments, social exclusion was manipulated through a Cyberball game (Williams & Jarvis, 2006). Many previous studies 1 (Fan & Jiang, 2018;Mathes & Schmidt, 2020;Yang et al, 2020) have used this tool and demonstrated its reliability. Furthermore, because we conducted online experiments, using Cyberball made it convenient for researchers and participants to complete the experimental process.…”
Section: Manipulation Technique (Cyberball)mentioning
confidence: 99%
“…Aghakhani and Main (2019); Baek et al (2018); Baek et al (2019); Bozkurt and Gligor (2019); Chen et al (2017); Dommer et al (2013); Duclos et al (2013); El Hazzouri et al (2017); Gao and Mattila (2016); Guèvremont and Grohmann (2016); Han et al (2015); Hu et al (2018); Jiang et al (2018); Jiang et al (2020); Jiao and Wang (2018); Kandaurova and Lee (2019); Khalifa and Shukla (2017); Kim, Park, et al (2020); Lee et al (2017); Lee and Shrum (2012); Liang et al (2018); Liang and Chang (2016); Liu et al (2021); Loveland et al (2010); Lu and Sinha (2017); Mead et al (2011); Mourey et al (2017); Newman et al (2019); Sinha and Lu (2019); Sinha and Wang (2013); Su et al (2017); Su et al (2019); Tezer and Bodur (2020); Thomas and Saenger (2020); Tunçel and Kavak (n.d.); Vinuales and Thomas (2021); Wan et al (2014); Wang et al (2012); Wang and Ding (2017); Wang and Lalwani (2019); Ward and Dahl (2014); Wu and Dodoo (2020); Xie, Chen and Guo (2020); Xu and Jin (2020); Yang et al (2020); Yi et al (2017)…”
Section: Methodsmentioning
confidence: 99%
“…Socially excluded individuals show proclivity toward engaging in risky consumption behaviour (Duclos et al, 2013;Mead et al, 2011;Yang et al, 2020), which can inflict harm on themselves or others.…”
Section: Efficacy Seeking Behaviourmentioning
confidence: 99%
“…It is worth noting, however, that the cushion hypothesis has been used to examine primarily objective financial outcomes associated with financial decisions (Grable et al, 2010;Yang et al, 2020). In their now seminal paper, Hsee and Weber (1999) noted that an individual's belief that a cushion is present influences financial management behavior such as a willingness to take investment risk.…”
Section: The Cushion Hypothesismentioning
confidence: 99%
“…Studies demonstrate that financial decision makers from collectivistic cultures are more likely to be risk seeking (Fan & Xiao, 2006;Schneider et al, 2017) and that this greater willingness to engage in risk-taking behavior can be explained by the perception of a cushion Schneider et al, 2017). Numerous studies confirm higher risk tolerance in Asian settings, with some studies examining the ability of the cushion hypothesis to explain objective markers of a household's financial situation (e.g., savings (see Yang et al, 2020)). However, few studies have been undertaken to investigate the relevance of the cushion hypothesis in explaining the effects of a willingness to take financial risk on financial well-being.…”
Section: Introductionmentioning
confidence: 99%